Design and implementation of 2.4GHz energy harvester - Lai, Zheng Yang (Nanyang Technological University, 2023)
In this technologically advanced world, research is conducted in search of future reliable and renewable energy source to power electrical devices, and Radio Frequency (RF) energy is viewed as one of the possible solutions. RF signals are constantly transmitted and received in today’s world mainly for wireless communications, therefore RF energy harvesting is a feasible concept. This project presents the fundamental concepts and processes of RF energy harvesting required to design and implement a 2.4GHz energy harvester. The RF energy harvester circuit consists of a Wi-Fi antenna, an impedance matching network, a rectifying circuit, and a boost converter circuit. All circuits are designed using Keysight’s Advanced Design System (ADS) software, and the Printed Circuit Board (PCB) of the harvester is then fabricated. The harvester will be tested, and its voltage output will be compared to the ideal results obtained from the simulation. Recommendations are explored to further improve the circuit and its efficiency.